The Ameliorative Effect of Litsea martabanica (Kurz) Hook. f. Leaf Water Extract on Chlorpyrifos-Induced Toxicity in Rats and Its Antioxidant Potentials - Weerakit Taychaworaditsakul; Suphunwadee Sawong; Supaporn Intatham; Sunee Chansakaow; Phraepakaporn Kunnaja; Teera Chewonarin; Kanjana Jaijoy; Absorn Wittayapraparat; Pedcharada Yusuk; Seewaboon Sireeratawong (Foods, 2024)
Litsea martabanica root’s antioxidant and acetylcholinesterase (AChE) activity showed promise as a pesticide detoxification agent in our previous study. In addition to its root, leaves can help alleviate pesticide exposure, although there is limited scientific evidence supporting their efficacy. However, the use of roots in several countries, such as Thailand, could contribute to environmental degradation, as highland communities traditionally used leaves instead of roots. This study aims to evaluate the antioxidant activity and anti-pesticide potential of water extract from L. martabanica leaves through in vitro and in vivo investigations. In the in vitro study, L. martabanica water extract and its fractions demonstrated antioxidant activity and induced apoptosis in hepatic satellite cells. In the in vivo study, treatment with the leaf extract led to increased AChE activity, decreased malondialdehyde (MDA) levels, increased superoxide dismutase (SOD) levels, and reduced glutathione in chlorpyrifos-exposed rats. Histopathological examination revealed that chlorpyrifos-treated rats exhibited liver cell damage, while treatment with the water extract of L. martabanica exhibited a protective effect on the liver. In conclusion, L. martabanica water extract exhibited antioxidant activity, enhanced AChE activity, and improved histopathological abnormalities in the liver.